Era Big Data. Czyli jak postęp technologiczny i metodologiczny wpływa na wybory prezydenckie? - Dajerling, Leonard (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
The aim of this article is to describe and analyze the possibilities of using Big Data techniques (collection and analysis of data) in order to win the presidential election by Donald Tramp. For this purpose, the author refers to the story of the development of the Internet as key to understanding the phenomenon of an unprecedented increase in the amount of information. As a result of the analyzed concept, changes are being made also in the field of methodology of sciences, especially concerning qualitative and quantitative approaches. Conclusions summarizing the article are theses behind the possibilities but also the dangers of data analysis techniques.